2017
DOI: 10.5539/ass.v13n9p33
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management Practice Influences Organizational Performance: A Case of a Vietnamese SME

Abstract: Quality Management Practice (QMP) has been proven its positive impact on organizational performance and received significant attention in recent years. However, there is little or no studies on QMP and organizational performance in Vietnam, specifically in Binh Duong. This research concentrated on finding the degree to which five elements of QMP namely Leadership, Strategic Planning, Process Management, Human Resource Management and Customer Satisfaction influence organizational performance within the scope of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This study contributes for better understanding on supply chain QM practices in Vietnam by emphasizing on the role of downstream QM practices on performance. Moreover, instead of considering operational performance as a single construct in previous studies (Nguyen and Ninh, 2017;Truong et al, 2017), this study measures operational performance by using three different dimensions that are quality, cost and delivery performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study contributes for better understanding on supply chain QM practices in Vietnam by emphasizing on the role of downstream QM practices on performance. Moreover, instead of considering operational performance as a single construct in previous studies (Nguyen and Ninh, 2017;Truong et al, 2017), this study measures operational performance by using three different dimensions that are quality, cost and delivery performance.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Panuwatwanich and Nguyen (2017) indicated that TQM practices in Vietnamese firms are mainly supported by internal focus culture, and TQM implementation was found to have a positive relationship with organizational performance. Nguyen and Ninh (2017) suggested that Vietnamese SMEs should focus on strengthening employees' mindset of continuous improvement to improve productivity and product quality. The study of Truong et al (2017) raises the importance of SCM practices, including top management support, customer focus, process control and improvement, supplier management.…”
Section: Supply Chain Quality Management Practicesmentioning
confidence: 99%
“…The results of previous studies found different findings such as the research conducted by Shan et al (2013) and Nguyen & Ninh (2017) revealing that process management as one of the principles of quality management has no effect on performance. In contrast to several other research results, it was found that process management practices are one of the factors in quality management that affect performance (Sabella et al, 2014;Ahmad et al, 2016;Al Damen, 2017;Nguyen & Ninh, 2017). These results are in line with Deming's concept of the concept of quality management that the implementation of effective quality management processes in the company will be followed by effective performance.…”
Section: Hypothesis Development Effect Of Process Management On Organ...mentioning
confidence: 84%
“…Data collection was carried out during the Covid 19 Pandemic in mid-2020 so that data collection was carried out via online, the data collected for use and processing in this study were 126 Head of Study Programs. The process management practice variable is measured by five indicators, namely clarity in providing work instructions, relatively stable work scheduling, monitoring and evaluation of work and automated work processes (Nguyen & Ninh, 2017). Knowledge creation (KC) is measured by 8 item indicators from SECI (socialization, externalization, combination, and internalization) (Nonaka & Von Krogh, 2009;Mehralian et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation